Online hostel room allocation system using codeigniter / Nor Isma Deana Jamil - Jamil, Nor Isma Deana (2020)
A manual way of paper-based system is believed to have a lot of disadvantages in management like wasting time, inefficient and costly. These factors consumes a lot of time to retrieve those paper documents when needed. The use of manual procedure can also lead to data loss as the paper document is easy to be broken or destroyed. Web-based application for Online Hostel Room Allocation System aims to modify the existing manual paper-based system management to site web-based application system. The purpose of the study is to establish and maintain an efficient registration and reservation college room system that can keep the processes in an orderly manner by using an electronic management system to save time and cost. The study involved three main phases which are the identification phase, the web-based application development phase and evaluation phase in part of the research methodology. PHP Codeigniter framework and Model View Controller (MVC) has been used together with the MySQL in order to complete the entire process of the system development. The MVC framework is also highlighted in this study according to the features itself that support the rapid development of the web-based system. The study involve usability and functionality testing by using unit testing, test script, and the distribution of post-task questionnaire respectively to the residents and staff in UiTM Perlis branch, Campus Arau. The data collected was analyzed and the result indicates over half of the respondents showed their agreements in using the developed system prototype. By using this system, it will be much easier for all college residents to reserve a college room. Therefore, the system will facilitate the college staff to access the information they need when the residents’ information is systematically kept in one place.